Bi-orthogonal wavelet transform based video watermarking (International Journal of Engineering and Computer Science, 2017)
This paper proposes a robust video watermarking algorithm based on Bi-orthogonal wavelet transform and singular value decomposition(SVD).This is a method that provides dual way authentication of video using QR code and Logo image which is more robust and accurate. Results show that the proposed algorithm has good robustness against common digital video attacks.Performances of the algorithm is evaluated with the help of various performance evaluation parameters.